Feiras de ciências e Semana Nacional de Ciência & Tecnologia como potenciais espaços formativos de formação continuada e contínua na prática pedagógica - Roehrs, Marfa Magali (2019)
The research was developed to comprehend the following problem: in which way the Science Fairs and SNC&T can be constituted in formative spaces of continuing and continued formation for teachers of the final years of Elementary and High School? The overall objective is to comprehend the potentialities of the Science Fairs and SNC&T as formative spaces of continuing and continued formation for teachers of the final years of Elementary and High School. Specifically, we made a study about the III FECIBB 2015, Science Faires, and SNC&T 2015 in the territory of Alto Paraguai (MT) considering the projects and activities on the dialogue with the normativeinstruments, identifying elements that facilitate the continued and continuing formation of the final years of Elementary and High School; and also identifying and analysing the teachers’ perceptions about the formative effect resultant in the participation on the III FECIBB, Science Faires in Alto Paraguai (MT) and SNC&T 2015. We used the dialectic/dialogical method in the freiriana perspective. The data was gathered trough a survey with Lickert scale and reunions with thematic discussions. We support the analysis in three arguments: that the Science Fairs constitute itself as a process of construction and development of knowledge and not as a exposing event; that the Science Fairs propitiate integration spaces with exchange of experience, dialogue, interdisciplinarity, collective study and partnership with the university and school community; and that the Science Fairs explore possibilities of access, construction and socialisation of Technology and Science. This Study sustain itself in theoretical speeches such as: Krasilchik (1985, 1987, 2000), Nóvoa (1992, 1995), Gil Pérez e Carvalho (1993), Oaigen (1995), Shön (1995), Freire (1975,1992,1996, 2001), Garcia (1999), Mancuso (2000),Tardif (2002, 2007, 2008, 2014), Santos (2007),Gonçalves (2008), Araújo e Caldeira (2009), Delizoicov, Angotti e Pernambuco (2011), Nardi (2001), Pereira et al. (2000) besides others. We took under consideration what was expressed on the official national documents as: LDB 9394/96, PNE2014-2024, rulling CNE/CP no 09/2001, the PCN-CN, the National Support Program for the Science Fairs of the Basic Education-FENACEB/MEC, the MCTI policy related with the popularization and diffusion of Science and Technology- MCTI/SECIS/ DEPDI, and other that permeate the documents. The sample was conducted with 27 teachers of the final years of the Elementary and High School, that attended, from 2014 to 2016 period, at least one Science Fair: III FECIBB 2015 and/or Science Faires in the territory of Alto Paraguai (MT), and the Week of Science and Tecnology 2015 in the territory of Alto Paraguai (MT) these events were made by UNEMAT Barra do Bugres (MT). The Science Fairs and the National Week of Science and Technology provide elements that approach the normative and conception of theoretic teachers about the continuing and continued formation of Basic education Teachers. It is relevant for contributing with the discussions about the formative spaces of continuing and continued formation of teachers and ads up the literature about national Science production in the Science Fairs and SNC&T subject, as a formative space for teachers.